KAJIAN SEMIOTIK SIMBOL DAN WARNA PADA KEMASAN GIZIDAT DALAM MEMBANGUN CITRA PRODUK - Suhariyanti, Suhariyanti (Bisnis-Net, 2025)
This study aims to examine the role of symbols and colors on the packaging of Gizidat products in building product image through a semiotic approach. Symbols and colors are chosen as the main focus because both are essential elements in visual communication that can influence consumer perception and attraction toward the product. The research method used is qualitative, employing semiotic analysis based on the theory of signs and meanings. The results show that the symbols on Gizidat packaging effectively convey clear messages and establish a strong product identity, while the use of colors provides psychological effects that support the product's image as healthy, trustworthy, and high-quality. The combination of symbols and colors on the packaging effectively strengthens the image of Gizidat products in the market, increases consumer appeal, and distinguishes it from competing products. This study recommends that the selection of semiotic elements on packaging should consider aspects of meaning communication in order to optimally support marketing strategies.